Insights Into the Mechanism of Tyrosine Nitration in Preventing β-Amyloid Aggregation in Alzheimer’s Disease - Zhao, Jie; Shi, Qihui; Zheng, Ye; Liu, Qiulian; He, Zhijun; Gao, Zhonghong; Liu, Qiong (Frontiers in Molecular Neuroscience, 2021)
Nitration of tyrosine at the tenth residue (Tyr10) in amyloid-β (Aβ) has been reported to reduce its aggregation and neurotoxicity in our previous studies. However, the exact mechanism remains unclear. Here we used Aβ1-42 peptide with differently modified forms at Tyr10 to investigate the molecular mechanism to fill this gap. By using immunofluorescent assay, we confirmed that nitrated Aβ was found in the cortex of 10-month-old triple transgenic mice of Alzheimer’s disease (AD). And then, we used surface enhanced Raman scattering method to demonstrate that the modification and mutation of Tyr10 in Aβ have little impact on conformational changes. Then, with the aids of fluorescence assays of thioflavin T and 4,4’-dianilino-1,1’-binaphthyl-5,5’-disulfonic acid, transmission electron microscopy, atomic force microscopy, and dynamic light scattering, we demonstrated that the deprotonation of the phenolic hydroxyl group of Tyr10 of Aβ is critical to Aβ fibrilization and aggregation. Based on previous researches and present results, we proposed that the negatively charged phenolic hydroxyl group induced by Tyr10 nitration at physiological pH could destroy the salt bridge between Glu11 and His6 or His13 and block the kink around Tyr10, thereby preventing Aβ fibrilization and aggregation. These findings provide us new insights into the relationship between Tyr10 nitration and Aβ aggregation, which would help to further understand that keeping the balance of nitric oxide in vivo is important for preventing AD.